Ligand-gated ion channel subunit partnerships: GABA-A receptor alpha6 subunit gene inactivation inhibits delta subunit expression - Jones,A; Korpi,ER; McKernan,RM; Pelz,R; Nusser,Z; Makela,R; Mellor,JR; Pollard,S; Bahn,S; Stephenson,FA; Randall,AD; Sieghart,W; et al. (J Neurosci, 1997)
Cerebellar granule cells express six GABA-A receptor subunits abundantly (alpha1, alpha6, beta2, beta3, gamma2, and delta) and assemble various pentameric receptor subtypes with unknown subunit compositions; however, the rules guiding receptor subunit assembly are unclear. Here, removal of intact alpha6 protein from cerebellar granule cells allowed perturbations in other subunit levels to be studied. Exon 8 of the mouse alpha6 subunit gene was disrupted by homologous recombination. In alpha6 -/- granule cells, the delta subunit was selectively degraded as seen by immunoprecipitation, immunocytochemistry, and immunoblot analysis with delta subunit-specific antibodies. The delta subunit mRNA was present at wild-type levels in the mutant granule cells, indicating a post-translational loss of the delta subunit. These results provide genetic evidence for a specific association between the alpha6 and delta subunits. Because in alpha6 -/- neurons the remaining alpha1, beta2/3, and gamma2 subunits cannot rescue the delta subunit, certain potential subunit combinations may not be found in wild-type cells.